Chromatin remodelling initiation in spermatids: differences among human males. (28th March 2013) - de, M.; Ramos, L.; Lacroix, R.; D'Hauwers, K.; Hendriks, J.C.M.; Kremer, J.A.M.; van der, J.; de, P.
Summary During the last phase of spermatogenesis, called spermiogenesis, the nucleosome‐based chromatin structure is replaced by a protamine‐based DNA packaging. Not much is known about the chromatin remodelling involved in humans and animals. Here, we have investigated initiation of chromatin remodelling over seven probands of which five were diagnosed with non‐obstructive azoospermia (NOA) and two with obstructive azoospermia (OA) (failed vaso‐vasostomy patients with proven fertility prior to vasectomy, Johnsen scores ≥9). Chromatin remodelling was studied evaluating the presence of nucleosomes, histone H3, pre‐protamine 2 and protamine 1. This approach was feasible since the local initiation of nucleosome eviction in the sub acrosomal domain, which was visible in alkaline nuclear spread preparations. The patterns of nucleosome and H3 loss were largely congruent. Nucleus wide incorporation of protamine 1 could already be observed at the late round spermatid stage. Both for nucleosome loss and for protamine 1 incorporation, there was distinct variation within and between probands. This did not relate to the efficiency of sperm production per meiocyte. Pre‐protamine 2 was always confined to the subacrosomal domain, confirming the role of this area in chromatin remodelling.